2021
DOI: 10.7150/ijms.58415
|View full text |Cite
|
Sign up to set email alerts
|

NSE, positively regulated by LINC00657-miR-93-5p axis, promotes small cell lung cancer (SCLC) invasion and epithelial-mesenchymal transition (EMT) process

Abstract: Background: Neuron specific enolase (NSE) is a specific biomarker for SCLC. However, the biological roles and aberrant expression of NSE in SCLC have not been well illustrated. Methods: The expression of NSE, miR-93-5p and LINC00657 in SCLC tissues and cell lines were detected using real time quantitative PCR (qRT-PCR) or immunohistochemistry. CCK8 assay was performed to detect cell proliferation. Cell migration and invasion capabilities were investigated by transwell assay. Epithelial-mesenchymal transition (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 55 publications
(44 reference statements)
1
4
0
Order By: Relevance
“…As shown in the results of the present study, serum tumor biomarkers, including CEA and NSE, were significant predictors in patients with PSCLC. In patients with an abnormal NSE level, a higher NSE level would indicate an increased likelihood of SCLC diagnosis, while the CEA level was higher in ADC than that in SCLC, which is consistent with previous studies ( 25 ). This study not only included serum tumor markers to explore the predictive markers but also considered the impact of other clinical factors such as smoking history, gender, and age on SCLC.…”
Section: Discussionsupporting
confidence: 92%
“…As shown in the results of the present study, serum tumor biomarkers, including CEA and NSE, were significant predictors in patients with PSCLC. In patients with an abnormal NSE level, a higher NSE level would indicate an increased likelihood of SCLC diagnosis, while the CEA level was higher in ADC than that in SCLC, which is consistent with previous studies ( 25 ). This study not only included serum tumor markers to explore the predictive markers but also considered the impact of other clinical factors such as smoking history, gender, and age on SCLC.…”
Section: Discussionsupporting
confidence: 92%
“…According to Zhang et al, the lncRNA NORAD promotes NSCLC progression by regulating the miR-26b-5p/COMMD8 axis, providing a potential novel target in NSCLC therapy [41]. LncRNA NORAD also promotes SCLC invasion and EMT by targeting the miR-93-5p/NSE axis [42]. Recently, Han et al suggested that lncRNA NORAD could be used as a core marker of COPD [43].…”
Section: Discussionmentioning
confidence: 99%
“…14 In recent years, many studies have shown that NSE is related to the diagnosis and staging of LC. 15 However, single tumor marker detection possesses lower sensitivity and specificity in the early diagnosis of LC, which has little application value in the early screening and diagnosis of LC, and the combined detection of multiple markers can make up for these defects. 16,17 So, it is important to find a better screening method to improve diagnostic rate of LC.…”
Section: Lc Have Recently Become Clearmentioning
confidence: 99%
“… 14 In recent years, many studies have shown that NSE is related to the diagnosis and staging of LC. 15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation